pharmaceutical-sciences 2019
DOI: 10.36468/pharmaceutical-sciences.535
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of Dimethyl Fumarate-loaded Polymeric Nanoparticles against Multiple Sclerosis

Abstract: Ojha et al.: Development of Dimethyl Fumarate-loaded Chitosan Nanoparticles The aim of the present study was to access the potential of dimethyl fumarate-loaded chitosan polymeric nanoparticles for the management of multiple sclerosis. Dimethyl fumarate-loaded chitosan nanoparticles were prepared by polyelectrolyte complex coaservation technique. The prepared nanoparticles were characterized and found to have an average particle size of 324 nm, zeta potential of-34.85 mV and a poly dispersity index of 0.367. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Presently, no effective drugs were approved for the therapy of the disease and few therapeutics are utilized to mitigate the symptoms of only the early stages of the disease with low evidence levels. Recently, dimethyl fumarate loaded solid lipid nanoparticles (Ojha & Kumar, 2018) and chitosan nanoparticles (Ojha et al, 2019) were reported to significantly increase the bioavailability and neuroprotective effects in rat models. This data presented that nanotechnology was a potential strategy with an enhanced circulation for the better treatment of multiple sclerosis.…”
Section: Nanotechnology-empowered Therapeutics In Other Neurodegenera...mentioning
confidence: 99%
“…Presently, no effective drugs were approved for the therapy of the disease and few therapeutics are utilized to mitigate the symptoms of only the early stages of the disease with low evidence levels. Recently, dimethyl fumarate loaded solid lipid nanoparticles (Ojha & Kumar, 2018) and chitosan nanoparticles (Ojha et al, 2019) were reported to significantly increase the bioavailability and neuroprotective effects in rat models. This data presented that nanotechnology was a potential strategy with an enhanced circulation for the better treatment of multiple sclerosis.…”
Section: Nanotechnology-empowered Therapeutics In Other Neurodegenera...mentioning
confidence: 99%
“…The main features of the disease reported to occur in early patients include cortical demyelination and meningeal inflammation ( Bø et al, 2003 ; Lucchinetti et al, 2011 ). Recent studies demonstrate that SL NPs and CS NPs can potentially increase the bioavailability and neuroprotective effects of a relapsing-MS drug dimethyl fumarate in rat model ( Ojha and Kumar, 2018 ; Ojha et al, 2019 ). Another study also suggests that glucocorticoids and inorganic–organic hybrid NPs can also be used to treat MS ( Montes-Cobos et al, 2017 ).…”
Section: Nanotechnology In Brain Diseases and Disordersmentioning
confidence: 99%
“…In an ethidium bromide-induced demyelination animal model study, Youssef et al 269 applied LINGO-1-directed siRNA-loaded chitosan nanoparticles and discovered that these nanomedicines could regulate the repair signal in histopathological sections, increase the expression of the pontine myelin basic protein, and reduce the activity of caspase-3 thus to induce the remyelination process and promote neuroprotection. Ojha et al 270 assessed the potential neuroprotective effect of dimethyl fumarate (DMF)-loaded chitosan (CS) dextran sulfate (DS) polymeric nanoparticles as therapeutic agents for a cuprizone model of MS. A significant increase in the locomotion score for the MS animal model indicated that the neuroprotective and therapeutic effect for MS was achieved by management of DMF-loaded CS-DS nanoparticles. These neuroprotective effects have also been confirmed by Elnaggar et al, 263 Hashemian et al, 261 Rong et al, 271 and Xu et al 272 in their studies on a variety of neurological disorders.…”
Section: Nanomedicines For Neuroprotection Inmentioning
confidence: 99%